2001
DOI: 10.3758/bf03192889
|View full text |Cite|
|
Sign up to set email alerts
|

How early maternal separation and juvenile experience with pups affect maternal behavior and emotionality in adult postpartum rats

Abstract: To assess the effects of preweaning and juvenile experiences on adult maternal behavior, two experiments were completed. In Experiment 1, pups were separated for long periods or short periods or were left undisturbed over the 1st week. Following weaning, the rats were exposed to foster pups over a 5-day period or were left undisturbed. There were no effects of early experience on juvenile behavior. In adult postpartum maternal tests, short separations reduced latencies to express maternal behaviors, whereas lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
2
24
0
1
Order By: Relevance
“…In a more recent study, although lactating females displayed increased pup-directed behavior (e.g., pup-licking) and decreased non-pup-directed behavior (e.g., burrowing) immediately following reunion of isolated (1-hr/day) and handled (5-10 min/day) litters, those females exposed to isolation as neonates did not show this pattern toward their own isolated litters (Kosten & Kehoe, 2010). On the other hand, 3 hr of daily maternal separation had few negative effects on later maternal behavior, and 15 min of daily separation enhanced later maternal behavior in adult rats (Rees & Fleming, 2001). Such differences in maternal responsiveness between studies may be explained, at least in part, by variations in duration of maternal separation, timing of the separation during development, number of separation episodes, isolation conditions, and/or choice of control group (Lehmann & Feldon, 2000).…”
Section: Discussionmentioning
confidence: 75%
“…In a more recent study, although lactating females displayed increased pup-directed behavior (e.g., pup-licking) and decreased non-pup-directed behavior (e.g., burrowing) immediately following reunion of isolated (1-hr/day) and handled (5-10 min/day) litters, those females exposed to isolation as neonates did not show this pattern toward their own isolated litters (Kosten & Kehoe, 2010). On the other hand, 3 hr of daily maternal separation had few negative effects on later maternal behavior, and 15 min of daily separation enhanced later maternal behavior in adult rats (Rees & Fleming, 2001). Such differences in maternal responsiveness between studies may be explained, at least in part, by variations in duration of maternal separation, timing of the separation during development, number of separation episodes, isolation conditions, and/or choice of control group (Lehmann & Feldon, 2000).…”
Section: Discussionmentioning
confidence: 75%
“…For instance, neonates that are separated from the maternal nest for 3 or 5 h daily show reduced maternal behaviors towards their own pups in adulthood Rees & Fleming, 2001). In our lab we have also employed a complete maternal deprivation paradigm (24 h daily).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, maternal separation as well as artificial rearing decrease maternal licking and crouching behavior in adulthood; however, only artificial rearing has a robust disruptive effect on juvenile maternal behavior (Gonzalez & Fleming, 2002;Gonzalez, Lovic, Ward, Wainwright, & Fleming, 2001;Lovic et al, 2001;Rees and Fleming, 2001). Whether these effects of artificial rearing on maternal behavior are due to changes in the HPA axis remain unclear, although research has shown that artificial rearing does not affect baseline or stress-induced levels of corticosterone (Burton, Chatterjee, Chatterjee-Chakraborty, Lovic, Grella, Steiner, & Fleming, 2007;Ward, Xing, Carnide, Slivchak, & Developmental Psychobiology Wainwright, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal separation disrupts adult postpartum maternal behavior (Boccia & Pedersen, 2001;Lovic et al, 2001), but has only subtle effects on juvenile maternal behavior Rees & Fleming, 2001). Whether early deprivation affects maternal behavior has not been investigated, although early deprivation transiently increases maternal behavior during maternal sensitization of the adult virgin rat (Rees & Fleming, unpublished observations) and may have the same effect on juvenile maternal behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation